2018
DOI: 10.3390/polym11010035
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Lignin Content on the Properties of Hemicellulose Hydrogels

Abstract: Hemicellulose is a promising renewable raw material for the production of hydrogels. This polysaccharide exists in large amounts in various waste streams, in which they are usually impure and heavily diluted. Several downstream processing methods can be combined to concentrate and purify the hemicellulose. However, such an approach can be costly; hence, the effect of impurities on the formation and properties of hydrogels must be determined. Lignin usually exists in these waste streams as a major impurity that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 36 publications
(67 reference statements)
1
16
0
Order By: Relevance
“…The proton NMR resonances in the anomeric region were assigned based on HSQC and confirmed by comparison with literature. 18,19,[59][60][61] The spectra recorded for both samples are similar confirming the similarity of the two samples. Hence, the SP is used as a template to describe assignments of the peaks.…”
Section: D and 2d Nmr Spectroscopysupporting
confidence: 66%
“…The proton NMR resonances in the anomeric region were assigned based on HSQC and confirmed by comparison with literature. 18,19,[59][60][61] The spectra recorded for both samples are similar confirming the similarity of the two samples. Hence, the SP is used as a template to describe assignments of the peaks.…”
Section: D and 2d Nmr Spectroscopysupporting
confidence: 66%
“…the constituents used to prepare mAPS x . That lignin and hemicellulose improve one another's thermal stability in such a way has been established for synthetic hydrogels 47 as well as for thermally-treated wood products. [48][49][50][51] The differential scanning calorimetry (DSC) data revealed that all of the materials exhibited cold crystallization peaks but no observable T g (full traces can be found in ESI, ‡ Fig.…”
Section: Paper Materials Advancesmentioning
confidence: 99%
“…The impact of water to the O-H stretching can be excluded as all of the samples were stored in a desiccator for drying. The areas between the peaks 1320 − cm 1 and 1410 − cm 1 ; 1410 − cm 1 and 1485 − cm 1 as well as 1485 − cm 1 and 1576 − cm 1 are intensified as well and can be attributed to skeletal vibration of phenolic compounds such as lignin 35 . Moreover, a new area around 1650 − cm 1 appeared which can be assigned to carbonyl containing components such as natural lignin or terpenoid extractives.…”
Section: Resultsmentioning
confidence: 99%